MEK1/2 inhibitor inhibits neointima formation by activating miR-126-3p/ C-X-C motif chemokine ligand 12 (CXCL12)/C-X-C motif chemokine receptor 4 (CXCR4) axis. Issue 4 (1st April 2022) - Yan, Yali; Zhu, Mengmeng; Ma, Jialing; He, Xiaoyu; Yang, Xiaoxiao; Xu, Hongmei; Jiang, Meixiu; Zhang, Shuang; Duan, Yajun; Han, Jihong; Chen, Yuanli
ABSTRACT: Endothelial dysfunction is an initial and essential step in vascular-remodeling diseases, including atherosclerosis and neointima formation. During vascular remodeling, activated endothelial cells can release pro-inflammatory factors that promote phenotypic switching of vascular smooth muscle cells (VSMCs) to the proliferative phenotype. We previously reported that MEK1/2 inhibitor, U0126, has a protective effect on the development of atherosclerosis and vascular calcification. However, the effect of MEK1/2 inhibitors on neointimal formation and the underlying mechanism is not fully understood. We determined that MEK1/2 inhibitor reduced carotid artery ligation-induced neointimal formation, while increased collagen and elastin levels and vascular integrality. Mechanistically, MEK1/2 inhibitor or ERK1/2 siRNA increased miR-126-3p level in endothelial cells, thereby inhibiting expression of regular of G-protein signaling 16 (RGS16), a miR-126-3p target gene, to activate the C-X-C motif chemokine ligand 12 (CXCL12)/C-X-C motif chemokine receptor 4 (CXCR4) signaling pathway. Accordingly, miR-126-3p was also increased by U0126 in serum and carotid artery. RGS16 was inhibited while CXCR4 and CXCL12 was increased by U0126 in neointimal areas, especially in the endothelium. Moreover, similar results were observed in atherosclerotic plaques of high-fat diet-fed apolipoprotein E deficiency (apoE −/− ) mice. In addition, vascular cell adhesion molecule 1 (VCAM-1), another miR-126-3p target gene, was reduced by U0126 in the neointimal areas, resulting reduced monocytes/macrophages accumulation. Taken together, our results indicate that MEK1/2 inhibitor can reduce neointima formation by activating endothelial miR-126-3p production to facilitate endothelium repair while reduce monocyte adhesion/infiltration. GRAPHICAL ABSTRACT: uf0001